“Is this science or can we get rid of it? - Prof. Dr. Tatjana Thimm (Via@)
The field of tourism sciences is currently dealing with numerous challenges. The path to becoming an independent field; determining its position in society, politics and the scientific community as well as the current threat from fake news are at the heart of this discourse analytical essay.